Neuromuscular motor tasks between skill and endurance trained athletes - Kumpulainen, S.; Mrachacz-Kersting, N.; Peltonen, J.; Linnamo, V.; Avela, J. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: It is well known that different types of physical exercise produce experiencespecific alterations in the corticomotorneuronal system (Adkins et al. 2006). Furthermore, previous study by Kumpulainen et al. 2014 showed that skill trained athletes have higher plasticity on the leg area of motor cortex compared to endurance trained athletes. Thus, it was hypothesized that skill and endurance trained athletes would perform differently in certain neuromuscular motor tasks. The purpose of this study was to compare 15 skill and 14 endurance trained athletes in 3 different motor tasks performed with plantar-flexors, which are training-relevant muscles for both groups. The tasks assessed rate of force development (RFD), reaction time, accuracy of force control and learning during the accuracy task.